Aeropuerto de Barajas (1998)
Ampliación por Richard Rogers Partnership>; Terminal de Cargas, Arq. Equipo AUIA
Keywords: BARAJAS; MADRID; ESPAÑA; AEROPUERTOS; AMPLIACION; ROGERS, RICHARD; ESTUDIO LAMELA; LAMELA, ANTONIO; INTERVENCIONES URBANAS